Climate Change and Pneumonia to Elederly: Systematic Review - Asriah Septiawati Jabani; Ramadhan Tosepu (Pustaka Bangsa Indonesia, 2026)
Pneumonia is a lower respiratory tract infection that affects approximately 450 million people worldwide and causes around 4 million deaths annually. The causative agents in adults include Streptococcus sp., Mycoplasma sp., Staphylococcus sp., Haemophilus sp., and Legionella sp. Aging leads to a decline in organ function and the immune system, making the elderly more susceptible to pneumonia. Global climate change also impacts human health, particularly through temperature, which influences bacterial growth, survival, and transmission. This study employs a literature review method using articles from Google Scholar with inclusion criteria focusing on the relationship between climate, pneumonia, and the elderly. The results indicate that climate change affects the survival of pneumonia-causing bacteria in the elderly. Therefore, climatic factors contribute to the increasing incidence of pneumonia, highlighting the need for early detection and mitigation efforts to reduce its impact.